2022
DOI: 10.1002/adhm.202201646
|View full text |Cite
|
Sign up to set email alerts
|

Protease‐Sensitive, VEGF‐Mimetic Peptide, and IKVAV Laminin‐Derived Peptide Sequences within Elastin‐Like Recombinamer Scaffolds Provide Spatiotemporally Synchronized Guidance of Angiogenesis and Neurogenesis

Abstract: Spatiotemporal control of vascularization and innervation is a desired hallmark in advanced tissue regeneration. For this purpose, we design a 3D model scaffold, based on elastin-like recombinamer (ELR) hydrogels. This contains two interior and well-defined areas, small cylinders, with differentiated bioactivities with respect to the bulk. Both are constructed on a protease sensitive ELR with a fast-proteolyzed domain, but one bears a VEGF-mimetic peptide (QK) and the other a laminin-derived pentapeptide (IKVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…During the last decades, cell–ECM interaction research has shown that when cell-adhesive molecules were spatially presented to the cells in different manners, they induced different patterns of cellular behavior [ 40 , 41 ]. In the case of CoC hydrogels, cell adhesion was achieved thanks to the contribution of the Caf1-YIGSR coating in the channel during the first coating step ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, cell–ECM interaction research has shown that when cell-adhesive molecules were spatially presented to the cells in different manners, they induced different patterns of cellular behavior [ 40 , 41 ]. In the case of CoC hydrogels, cell adhesion was achieved thanks to the contribution of the Caf1-YIGSR coating in the channel during the first coating step ( Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, VEGF-mimetic peptide and elastin-like polypeptide-based hydrogels, in combination with integrin binding motifs and urokinase-protease-sensitive sequences, synergistically induced cell infiltration and angiogenesis without the formation of fibrotic tissue in vivo. 61 Moreover, the combination of different integrin-adhesion ligands presenting a high binding affinity and selectivity for α v β 3 , α 5 β 1 , or α 4 β 1 facilitated the dynamic capture and adhesion of endothelial colony forming cells under shear flow mimicking blood flow. 62…”
Section: Strategies For Manipulating Physical or Biochemical Hydrogel...mentioning
confidence: 99%
“…[22] Likewise, Fernando et al reported a 3D hydrogel scaffold containing the IKVAV peptide promoted axon spreading neurogenesis in mice. [23] However, to the best of our knowledge, no previous study has prepared engineered exosomes grafted with IKVAV and taken their advantages for SCI repair.…”
Section: Introductionmentioning
confidence: 99%